Case report: HLA-B35-associated optic neuritis - Guillot, Florian H.; Carey, Andrew R. (Frontiers in Ophthalmology, 2024)
PurposeTo describe a unique presentation of optic neuritis associated with positive HLA-B35.ObservationsA woman presented with unilateral retro-orbital pain, mildly decreased vision, and optic disc edema with new-onset aphthous ulcers. Color vision was preserved, and no visual field deficits were noted. Diagnostic imaging demonstrated retrobulbar optic nerve enhancement, with genetic testing revealing HLA-B35 positivity. Treatment with high-dose oral steroids for 3 days resolved all symptoms, and the patient remained stable for at least 2 months.Conclusions and importanceIn addition to rheumatic conditions and oral lesions, HLA-B35 can be linked to optic neuritis. This relationship highlights the need to further explore genetic risk factors associated with optic neuritis and the potential need for human leukocyte antigen (HLA) testing in unusual cases of optic neuritis.